Protection of Consumer Rights in Online Buying and Selling: Analysis of the DSN-MUI Fatwa and Its Implementation in Sharia E-Commerce - Ghina Khairiyati Salsabila; Rahmatillah Rahmatillah (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The development of digital technology has driven the growth of online buying and selling transactions significantly, including in the scope of sharia e-commerce. This phenomenon raises new challenges related to the protection of consumer rights in accordance with sharia principles. This study aims to analyze the protection of consumer rights in the practice of online buying and selling based on the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) and examine its implementation on sharia e-commerce platforms in Indonesia. The method used is qualitative with a normative and sociological approach. The data source was obtained through a study of documents on relevant DSN-MUI fatwas, as well as interviews with managers and users of sharia e-commerce platforms. The results of the study show that the DSN-MUI fatwa has provided a normative basis related to justice, information disclosure, and the prohibition of gharar elements in online transactions. However, its implementation in the field still faces a number of obstacles such as weak supervision, lack of consumer literacy, and the absence of specific technical regulations in sharia e-commerce. Therefore, there needs to be synergy between Islamic financial authorities, industry players, and consumers to strengthen the protection of consumer rights holistically in online buying and selling based on sharia principles.